Proceedings of the Annual PL/DARPA Seismic Research Symposium (14th) Held in Tucson, AZ on 16-18 September 1992 - Lewkowicz, James F.; McPhetres, Jeanne M. (1992)
Partial contents of papers presented include: A Generalized Likelihood Ratio Test in Outlier Detection or Script Matching; Analysis of Regional Bodywave Phases from Earthquakes in West China; Numerical Models of Quarry Blast Sources; Regional Seismic Event Discriminants: What Works, What Doesn't and Why; Seismic Discrimination of Rockbursts in Mines; Deep Seismic Soundings in Northern Eurasia: Interpretation of the Murmansk-Kizil Ultra-Long- Range Profile; Non-Linear Attenuation in the Near Source Region: Characterization of Hysteresis in the Deformation of Rock Joints; Epicentral Azimuth Determination by Mini Array Processing; Source Function Deconvolution of Delay-Fired Explosions and Earthquakes at Regional Distances; Regional Wave Attenuation in Eurasia; Effects of an Irregular Free Surface and Moho on Regional Wave Propagation; Global Seismic Evidence Combination; Generalized Ray/Born Synthesis of Complete Regional Seismograms in Three-Dimensional Crustal Models; An X-Windows Graphics Tool to Compute Synthetic Seismograms for 2-D models Using Gaussian Beams; Seismic Array Study of the Baikal Rift Zone, Siberia; Numerical Simulation of Nonlinear Attenuation Using an Endochronic Formulation; Applications of Array Spectral Factorization Methods to Regional Seismic Discrimination and Three-Component Processing; A Network-Accessible Geological and Geophysical Database for Eurasia; Multivariate Seismic Calibration for the Novaya Zemlya Test Site; Ground-Truth Data for Seismic Discrimination Research.